POLA ASUH ORANGTUA KRISTEN TERHADAP KARAKTER ANAK MENURUT 1 KORINTUS 13 - Eliana Reva Yosina; Fianus Tandiongan; David Priyo Susilo (STT Kristus Alfa Omega, 2022)
Based on observation and result of parent and child research questionnaires, researcher found that parent have not implemented parenting according to Christians values, and child’s character have not according 1 Corinthians 13. Research objectives is to find out the level parenting of Chistian family, find out the level of child’s character, and parenting of family Christian to child’s character. Research methods is quantitative descriptive- correlation. Analysis value from the level parenting of Christian family very good or 85,48%, the level child’s character is good or 76,67%, and parenting of family Christian to child’s character is very low or 13,1%.